Implementation of the Religious Moderation Program at Private Madrasah Aliyah in Lebak District, Banten Province - Depi Akbar; Wawan Wahyudin; Apud (Formosa Journal of Sustainable Research, 2022)
This study aims to describe the implementation of religious moderation policies, find out strategies for implementing religious moderation policies and find out the supporting and inhibiting factors in implementing religious moderation by teachers at Madrasah Aliyah Nurul Hidayah Lebakjaha and Madrasa Aliyah Daar El-Ishlah Malingping Lebak Regency. This study uses a descriptive qualitative approach using observation data collection methods, interviews and documentation. The technical stages of data analysis included data reduction, data presentation and data verification, while checking the reliability of the data was carried out by extending participation, accuracy of observations, triangulation and consulting supervisors. The results of the study concluded that: (1) Implementation of strategies to strengthen religious moderation in madrasas has been integrated with religious moderation values ​​through teaching and learning activities (KBM), extracurricular activities (SKI), and habituation activities. (2) The strategy for strengthening religious moderation in Madrasas is that the efforts made by the heads of madrasah heads are as follows: (a) Persuasion approach, (b) Deideologization of teachers who are exposed to extreme views, (c) Integrative policy of religious moderation, ( d) Synergizing learning programs with activities outside of learning, and supporting the implementation of religious moderation in these madrasas, including: Vision and mission of the madrasa, madrasa regulations, community interest, a conducive atmosphere of the madrasa, infrastructure facilities, achievement motivation, and the academic qualifications of the supervisor teacher while the factors the obstacles are the inadequate condition of the library, social/mass media, community environment, and family environment.